2021
DOI: 10.1007/s13762-021-03455-3
|View full text |Cite
|
Sign up to set email alerts
|

Modeling-based performance evaluation of novel cascade cum trickling filter wastewater treatment system

Abstract: Optimization of operational parameters of wastewater treatment system using the modeling technique may lead to enhance the system's operational and treatment efficiency. The present research was carried out to investigate the treatment efficiency of conventional trickling filter (CTF) and cascade cum trickling filter (CCTF) for treatment of domestic wastewater. Both the systems (CTF and CCTF) were operated for a period of four months under temperature range of 21-48 °C. The maize cob (MC) and date palm fibre (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…There is a lack of sufficient data in the literature for comparison, and few studies have reported values that vary significantly because of the difference in scale and scope of the study. Kanwar et al (2022) found that the power consumption of both conventional and cascade cum trickling filters was in the range of 0.3-0.6 kWh/m 3 . m 3 ) membrane bioreactors (Garfí et al, 2017;Kanwar et al, 2019;Martin et al, 2011).…”
Section: Energy Consumption For Tuww Reusementioning
confidence: 99%
“…There is a lack of sufficient data in the literature for comparison, and few studies have reported values that vary significantly because of the difference in scale and scope of the study. Kanwar et al (2022) found that the power consumption of both conventional and cascade cum trickling filters was in the range of 0.3-0.6 kWh/m 3 . m 3 ) membrane bioreactors (Garfí et al, 2017;Kanwar et al, 2019;Martin et al, 2011).…”
Section: Energy Consumption For Tuww Reusementioning
confidence: 99%